Use of Oral Nutritional Supplements in Neurology: General Principles, Special Practices - Mehmet Akif Topçuoğlu; Ethem Murat Arsava; Esen Saka (Türk Nöroloji Dergisi, 2021)
There is convincing scientific evidence that the use of oral nutritional supplements (ONS) is advantageous in patients with disabling neurologic diseases such as stroke, dementia, amyotrophic lateral sclerosis, multiple sclerosis or Parkinson’s disease, and also in older patients with a diagnosis of malnutrition or just risk of malnutrition, and in all these cases accompanied with insufficient oral food intake or during a condition such as infection, trauma or hospitalization that may pose an increased malnutrition risk along. A wide spectrum of commercial formulas ensuring adequate patient adaptation and toleration are available. For ONS supply to be beneficial, a person at risk of malnutrition or with the diagnosis of malnutrition should consume ONS containing at least 400 kcal of energy and 30 grams of protein per day for a minimum of 1 month. ONS should not reduce the amount of normal daily food intake. If useful, ONS should be continued within the scope of predetermined goals. Supplementation of ONS is an economical and useful neurology practice.